Advertising Explained. - Caton, Dennis (Routledge library editions. Advertising, 2013)
This work explains the various elements which go to the making of a successful advertising campaign - the planning, research and discussion - and gives some helpful information about advertising media, the creation of advertisements, about printing processes and mechanical production. It touches upon marketing and distribution and shows how these things must have a direct bearing on any well-framed advertising policy.The work of the Advertising Agency is fully described and there is some interesting advice about overseas advertising.Advertising Explained contains 27 ill.